Roles of plant growth substance in callus induction of Achyranthes bidentata - Duan, Hongying; Ding, Weikai; Song, Jianying; Xu, Jiaming; Wang, Huina; Zhu, Yanqiu; Liu, Wenxiao; Zhou, Yanqing (Research in Plant Biology, 2016)
Â Â Â In this research, callus from leaves, petioles and stems of Achyranthes bidentata was evidently initiated by plant growth substance, in which 2,4-dichlorophenoxyacetic acid (2,4-D) was very important to callus induction, but effects of other plant growth substances were various, and the optimum combination of plant growth substances for callus induction from leaves, petioles and stems was respectively obtained. Compared with callus induction from leaves and petioles, callus induction from stems was easier, and the higher induction rate and bigger mass of callus from stems were obtained. This study showed that the dedifferentiation capacity of various explants from Achyranthes bidentata was obviously different, and effects of plant growth substance on callus induction from various explants of Achyranthes bidentata were significantly diverse.